2018
DOI: 10.4103/am.am_37_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Opportunistic Enteric Parasitic Infections in HIV Infected Individuals and their correlation with CD4 Count

Abstract: HIV infection is a worldwide phenomenon with serious public health implications. UNAIDS data 2017 stated that 36.7 million people are living with HIV infection and approximately one million death are caused due to AIDS-related illness in the year 2016. [1] Although the prevalence of HIV infection in India is less compared to other countries, currently 21.7 lakhs people carry HIV infection in India. [2] Diarrhea is a leading cause of substantial morbidity and mortality in persons infected with HIV, occurring at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Hence, these superimposed infections are occurring due to the extent of deterioration of the immune system and then could predict the prevalence of enteric parasites. 27,38 The current study also revealed that children who had a viral load >1,000 copies/mL were 1.8-times more likely to be infected with intestinal parasites (AOR=1.80; 95% CI=1.67-4.19; P=0.01). Despite the absence of a significant association, this is in agreement with the study conducted by Fregonesi et al, 39 which suggested that a high percentage of parasite-infected children were observed among children with high viral loads.…”
Section: Discussionsupporting
confidence: 53%
“…Hence, these superimposed infections are occurring due to the extent of deterioration of the immune system and then could predict the prevalence of enteric parasites. 27,38 The current study also revealed that children who had a viral load >1,000 copies/mL were 1.8-times more likely to be infected with intestinal parasites (AOR=1.80; 95% CI=1.67-4.19; P=0.01). Despite the absence of a significant association, this is in agreement with the study conducted by Fregonesi et al, 39 which suggested that a high percentage of parasite-infected children were observed among children with high viral loads.…”
Section: Discussionsupporting
confidence: 53%
“…HIV-infected persons are at higher risk for undernutrition, and certain conditions can magnify the risk, such as anorexia, di culty swallowing or painful swallowing, malabsorption and diarrhea, altered metabolism of nutrients, increased utilization of nutrients, and greater loss of nutrients (4). Not only this but also, there are many factors associated with HIV/AIDS undernutrition among them household food insecurity, lack of nutritional counseling, educational status, and economic status are evidenced by many studies (6,10,14,15).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adherence to ART drugs is low in undernourished HIV/AIDS patients (13).HIV-infected persons are at higher risk for undernutrition, and certain conditions can magnify the risk, such as anorexia, di culty swallowing or painful swallowing, malabsorption and diarrhea, altered metabolism of nutrients, increased utilization of nutrients, and greater loss of nutrients (4). Not only this but also, there are many factors associated with HIV/AIDS undernutrition among them household food insecurity, lack of nutritional counseling, educational status, and economic status are evidenced by many studies (6,10,14,15).Many studies were conducted on HIV/AIDS patients but since the dispute undernutrition is unanswered and still there is a lack of information in the Ethiopian context further investigation will be needed. Again, there is a difference between malnutrition and undernutrition but most of the studies use malnutrition and undernutrition interchangeably as the same term.…”
mentioning
confidence: 99%
“…It is an opportunistic parasite with worldwide distribution and causes a self-limiting diarrhoea in immunocompetent individuals. However, in immunocompromised subjects (patients with AIDS, children with malnutrition and the elderly), the disease can be severe, prolonged and lethal (22)(23)(24). The defence mechanisms responsible for limitation of disease in humans have not been fully characterized, due to the self-limiting nature of the disease in healthy individuals and general underdiagnosis of Cryptosporidium infection.…”
Section: Introductionmentioning
confidence: 99%